Bluebirds and Other Cavity-Nesting Birds: Leader’s Guide - Loretta Rodriguez; Joy Jordan; Mark E. Hostetler; Christina Packard; Jessica Kochert (EDIS)
4HWLL30, a 40-page illustrated guide by Loretta Rodriguez, Jessica Kochert, Joy Jordan, Christina Packard, and Mark Hostetler, provides group leaders additional information and group activities to support a bluebird project (4HWLM20). The guide includes ready-to-use skill-a-thon resource materials and facilitator tips for each activity. Includes references. Published by the Florida 4-H Youth Development Program, January 2010.